2005
DOI: 10.1248/bpb.28.233
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Gumiganghwaltang through the Inhibition of Nuclear Factor-κB Activation in Peritoneal Macrophages

Abstract: Gumiganghwaltang (GMGHT) consists of 9 different herbs and is a Korean herbal prescription, which has been commonly used to treat a cold and inflammatory diseases in Korea. However, it is still unclear how it regulates the immune or inflammatory responses.Macrophage activation is known to play an important role in the inflammatory process 1,2) and produce potent proinflammatory cytokines such as tumor necrosis factor (TNF)-a, and interleukin (IL)-6 which induce inflammation and recruit other immune cells, e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…candidates [22] and traditional herbal medicines [23]. In the present study, we found that AKEE suppressed LPSinduced IL-6 and TNF-α production in a concentrationdependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…candidates [22] and traditional herbal medicines [23]. In the present study, we found that AKEE suppressed LPSinduced IL-6 and TNF-α production in a concentrationdependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…IL-6 is believed to be an endogenous mediator of LPS-induced fever. Recently, new approaches for the use of Chinese herbal plants to prevent and treat inflammatory responses by inhibiting inflammatory cytokines, such as TNF-α, IL-1β, and IL-6, have become an important area of investigation, as have their associated complications [23]. In the present study, it was found that schisantherin A also significantly inhibits TNF-α and IL-6 release that is not due to schisantherin A cytotoxicity, as assessed by the MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the new approaches on the use of herbal products for the treatment of inflammatory diseases are being practiced in traditional medicine but without understanding their associated complications. Hence, our study focuses on the mechanism of action of bioflavonoid the apigenin, which is extensively used in alleviating the inflammatory diseases by inhibiting cytokines and TNF-a [26]. Apigenin is an anti-inflammatory molecule found in fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%